Hypoplastic Left Ventricle: Hypoplastic Left Heart Complex. Issue 5 (September 2022) - Tchervenkov, Christo I.; Tang, Richard; Jacobs, Jeffrey P.
Hypoplastic left heart syndrome (HLHS) without intrinsic valvar stenosis or atresia is synonymous with the term hypoplastic left heart complex (HLHC) and is defined as a cardiac malformation at the milder end of the spectrum of HLHS with normally aligned great arteries without a common atrioventricular junction, characterized by underdevelopment of the left heart with significant hypoplasia of the left ventricle and hypoplasia of the aortic or mitral valve, or both valves, in the absence of intrinsic valvar stenosis or atresia, and with hypoplasia of the ascending aorta and aortic arch. This article describes the definitions, nomenclature, and classification of HLHC; the indications and contraindications for biventricular repair of HLHC; the surgical treatment of HLHC; and the associated outcomes.